Du devenir du ressenti et de la parole de l'enfant : l'exemple des activités périscolaires dans une ville en France - Gaëlle Espinosa; Véronique Barthélémy; Benoit Dejaiffe (Université de Provence, 2021)
The French law on school rhythms (MEN, 2013) aims in particular at the success of all pupils in primary school and establishes new extracurricular activities. These activities are now part of the pupil's educational experience. If the child, the main target and actor of these activities, is excluded from debates and decisions concerning him (MEN, 2017), our work considers him as a key informant. The objective of this paper is to contribute to a better understanding of what children participating in activities say live and feel in these activities in order to better understand the reasons for their taste and interest in these activities. 26 children were interviewed. Our analyses reveal the children's ability to listen to their internal sensations and to express themselves on these sensations, presenting reasons for their taste and interest in activities and highlighting the paradox of not taking their words into account in decisions concerning these activities. Then we discuss the reasons for this disregard.